Case Report: Investigating the feasibility of virtual reality meditation for managing migraine in females: a multiple baseline replicated case study - Bell, Laura; Walters, Julie L; Macintyre, Erin; Harvie, Daniel S (Frontiers in Virtual Reality, 2025)
BackgroundVirtual reality offers a potential way to facilitate amplified forms of meditation and distraction, potentially inducing greater states of stress and pain reduction. It is an intriguing possibility that VR-based meditation could disrupt migraine neurophysiology.ObjectiveWe aimed to explore the feasibility, usability, and potential benefits of home-based virtual reality-delivered meditation in migraine management.MethodsA multiple baseline replicated Single-Case Experimental Design using an A-B-A (A1-Baseline, B-Intervention, A2-Follow-up) procedure was employed. Two participants underwent serial observations before, during, and after an intervention involving daily meditations at points relevant to migraine onset and peak. Systematic visual analysis of the data was supported by Tau-U statistical analysis. Treatment adherence data and questionaries were used to further interrogate feasibility.ResultsVisual analysis suggested no apparent change in pain intensity and migraine frequency across the study. The Tau-U index supported this finding, confirming that pain reports were non-phase-dependent (all ps > 0.4). Adherence to the daily meditation was high (>89%), but adherence to meditations at onset and peak pain was low (0%–43%). Both participants reported high System Usability Scale scores (>80/100). One participant reported “Fairly good improvement” in “Global Perceived Effect”, but corresponding change in other quality of life, psychological or pain-related outcomes was not seen Implications: While it is premature to exclude a role for virtual reality meditation in migraine management in specific individuals, this case series provides no support for a potential benefit although utility in some individuals cannot be ruled out by the current design. Moreover, we highlight potential issues related to implementing VR-based interventions in groups experiencing migraine pain, particularly regarding protocol adherence at migraine onset and peak pain.